The environmental fate of perfluoroalkyl acids in East China Sea sediments: Influence of depositional settings and sediment transport processes - Mingzhi Liu; Zhongyong Yan; Ningning Zhu; Fan Yang; Guoquan Wang; Xiaohua Wang; Qinglin Mu; Oliver A.H. Jones; Xibin Han; Chunfang Zhang (Water Research, 2026)

A predictive control method for ship dynamic positioning using a two-layer model based on a predefined time non-singular fast-terminating sliding mode - Fan Yang; Minjie Zheng; Guoquan Chen; Hong Zhu; Shenhua Yang (Ocean Engineering, 2026)

Fixed-Time Nonsingular Fast Terminal Sliding Mode Tracking Control for Unmanned Surface Vehicle Based on Disturbance Observer - Minjie Zheng; Fan Yang; Yulai Su; Guoquan Chen; Hong Zhu; Shenhua Yang (Journal of Marine Science and Engineering, 2026)
This paper investigates the trajectory tracking control problem for an unmanned surface vehicle (USV) subject to unknown time-varying environmental disturbances and the challenge of ensuring fast convergence while avoiding singularities. A novel fixed-time nonsingular fast terminal sliding mode (NFTSM) control scheme, integrated with a fixed-time disturbance observer (DOB), is proposed to achieve high-precision and robust tracking. The control architecture consists of three key components: (i) a fixed-time virtual velocity control law designed to ensure that position errors converge to zero within a fixed time even when velocity errors vanish, thereby preventing slow convergence; (ii) a nonsingular fast terminal sliding surface that eliminates the singularity issue inherent in traditional terminal sliding mode and guarantees that the USV state converges to the desired trajectory within a fixed time independent of initial conditions; and (iii) a fixed-time DOB that accurately estimates and compensates for external disturbances, with estimation errors proven to converge to zero in a fixed time. The stability and fixed-time convergence of the closed-loop system are rigorously established using Lyapunov theory. Comparative simulations, conducted under external disturbances on the Cybership II model, demonstrate that the proposed NFTSMC strategy significantly outperforms conventional sliding mode control (SMC) and nonsingular terminal sliding mode control (NTSMC). Specifically, the proposed scheme reduces the integral of absolute error (IAE) for position tracking by over 60% and the integral of time-weighted absolute error (ITAE) by more than 30% compared to SMC, while achieving smoother control inputs and stronger disturbance rejection. These results highlight the superior convergence speed, tracking accuracy, and robustness of the proposed controller, underscoring its originality and practical value for USV autonomous navigation.

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Magnetic traction and molecular lock-key: Nano-intelligent nanobot overcomes glioblastoma ferroptosis resistance to activate ferroptosis-immune - Peng Ye; Tianyu Su; Kai Wang; Dehong Yu; Minghao Chao; Liying Fan; Guoquan Wu; Guanghui Wang; Fenglei Gao; Lei Hua (Chemical Engineering Journal, 2026)

MiR-192-5p protects hexavalent chromium-induced apoptosis in renal epithelial cells by inhibiting p53 signaling pathway - Leying Wen; Kai Cai; Caixia Fan; Lifang Jin; Guoquan Fu; Junyan Yan (Molecular & Cellular Toxicology, 2026)

Ship target detection algorithm in remote sensing images based on improved YOLO11s - Zening Wang; Wenjuan Li; Yangquan Fan; Liyuan Wang; Guoquan Yao (Ocean Engineering, 2026)

Wind-tide modulated net ecosystem metabolism in a Changjiang River Estuary aquaculture zone during mid-autumn - Di Wu; Kui Wang; Guoquan Wang; Qinglin Mu; Wei Fan; Dawei Xu (Marine Environmental Research, 2025)

Noncovalently functionalized carbon microspheres for separating no-carrier added 177Lu from real neutron-irradiated 176Yb target - Guoquan Ma; Haiyue Peng; Xisheng Fan; Yuqi Guo; Yang Li; Jing Gao; Yingjiang Hu; Bo Li; Yuanyou Yang; Jingsong Zhang; Lijian Ma; Ning Liu; et al. (Chemical Engineering Journal, 2025)

Influences of permeable pavements with different hydraulic properties on evaporative cooling and outdoor thermal environment: Field experiments - Jiahong Zhao; Jiang Lu; Jian Ge; Yifan Fan; Haoxian Wang; Muye Gu; Yucong Xue; Yujie Zhao; Guoquan Lv; Haiqin Lin; Kang Zhao; Xiaoyu Luo (Building and Environment, 2025)

Genetic diversity and genetic structure of local pear cultivars in Xinjiang based on SNP markers - Qingrui Bi; Dongsheng Cui; Guoquan Fan; Shikui Zhang; Shaopeng Wang; Yingying Niu; Shirong Zhao (South African Journal of Botany, 2024)

Clarifying the impact of engine operating parameters of heavy-duty diesel vehicles on NOx and CO2 emissions using multimodal fusion methods - Tao Li; Xin Lou; Zhuoqian Yang; Chaojie Fan; Baoli Gong; Guoquan Xie; Jing Zhang; Kui Wang; Honghao Zhang; Yong Peng (Science of The Total Environment, 2024)

“Resource-Conserving” engineered nanoparticles Mediate disulfidptosis by overcoming resistance to ferroptosis for antitumor immunotherapy - Tianyu Su; Guoquan Wu; Peng Zhou; Jin Wang; Xu Zhu; Liying Fan; Hanrong Yan; Guangyu Ma; Zhao Liu; Xiang Wang; Fenglei Gao (Chemical Engineering Journal, 2024)

A reverberating triple AND logic gate nanomachine for intracellular multi-enzyme tracking and MicroRNA detection - Xu Zhu; Jun Zhu; Jin Wang; Guoquan Wu; Tianyu Su; Liying Fan; Junjie Li; Yufan Liu; Dehong Yu; Rongrong Sun; Ning Xin; Fenglei Gao (Chemical Engineering Journal, 2024)

Effect of faba bean Vicia faba L. water/alcohol extract on growth performance, antioxidant capacity, textural properties, and collagen deposition in the swim bladder of juvenile Nibea coibor - Haoji Guo; Guoquan Liu; Mengdu Tian; Chunsheng Liu; Haoran Zhang; Shuqi Wang; Xiaobo Wen; Fan Lin (Fish Physiology and Biochemistry, 2024)

Dietary Saccharina japonica is a natural and effective tool to fortify marine teleost black sea bream fillets with iodine: effects on growth, flesh quality, and serum thyroid hormones - Chuanqi Yu; Guoquan Liu; Jun Yu; Fan Lin; Xiaobo Wen (Journal of Applied Phycology, 2020)

Complete genome sequence of a novel bacteriophage infecting Bradyrhizobium diazoefficiens USDA110 - Junjie Liu; Hao Yu; Yong Huang; Zhenhua Yu; Guoquan Fan; Jian Jin; Xiaobing Liu; Guanghua Wang (Science China Life Sciences, 2018)

Complete genome sequence of a novel lytic bacteriophage isolated from Ralstonia solanacearum - Jingfang Su; Hongwei Sun; Junjie Liu; Zhaokui Guo; Guoquan Fan; Gang Gu; Guanghua Wang (Archives of Virology, 2017)

Development and application of a universal and simplified multiplex RT-PCR assay to detect five potato viruses - Wei Zhang; Zhixiang Zhang; Guoquan Fan; Yanling Gao; Jingzhi Wen; Yanju Bai; Cailing Qiu; Shu Zhang; Yu Shen; Xianxin Meng (Journal of General Plant Pathology, 2017)